Synthèse de nouveaux dérivés chalcones benzimidazoliques contenant du 1,2,3-triazoles via la Réaction de Click et étude de leurs activités biologiques - Djemoui, Amar (Universty of Eloued جامعة الشهيد حمه لخضر, 2019)
الملخص: في هذا العمل تم تصنيع سلسلة من مركبات هجين تريازول-بنزيميدازول-كالكون عن طريق كيمياء النقر ، بين مشتقات أزيدية اروماتية مختلفة وعدة مركبات بنزيميدازولية مستبدلة تحمل شق كالكون. تم تحضير ألكينات البدء عن طريق ألكلة النيتروجين باستعمال أساس كمحفز لمركبات بنزيميدازولية-كالكونية سابقة التركيب. بواسطة الرنين المغناطيسي النووي (1D ، 2D) وتقنيات الطيف الكتلي تم تمييز جميع المركبات . بواسطة ارتباطات HMBC تم تحديد أيزومر-4-1 تريازول-بنزيميدازول-شالكون الوحيد.اهتممنا أيضا في هذه الأطروحة لتوليف مشتقات اميدازو بيريميدين جديدة بواسطة تكثيف بسيط ل 2-أمينوبنزميدازول على مشتقات بنزيميدازول-الكالكون. قمنا ايضا بدراسة الفعالية المضادة للباكتيرايا و المضادة للسرطان (سرطان الثدي و سرطان المثانة) لبعض مشتقات هجين تريازول-بنزيميدازول-كالكون فكانت الفعالية متوسطة الى فوق المتوسطة على الغالب. Abstract:In this work novel series of triazole-benzimidazole-chalcone hybrid compounds have been synthesized via click chemistry, between different aromatic azide derivatives and several substituted benzimidazole terminal alkynes bearing a chalcone moiety. The starting alkynes are prepared via base-catalyzed nitrogen alkylation of a pre-synthetized benzimidazole-chalcone substrates. All the intermediates as well as the final products are fully characterized by 1D and 2D NMR and mass spectrometry techniques. HMBC correlations permits the identification of unique 1,4-disubistitued triazole-benzimidazole-chalcone isomer.We are also interested in this thesis to the synthesis of new imidazo [1,2-a] pyrimidine derivatives by a simple condensation of 2-aminobenzimidazole with benzimidazole-chalcone derivatives. Antibacterial and anticancer biological tests (breast cancer and prostate cancer) of a few triazole-benzimidazole-chalcone hybrids have been performed, the results obtained are moderate.
أطروحة دكتوراه تخصص كيمياء عضوية صناعية في العلوم الدقيقة
Keywords: هجين تريازول-بنزيميدازول-كالكون ، كيمياء النقر، ألكينات، اميدازو بيريميدين ، المضادة للسرطان; triazole-benzimidazole-chalcone hybrid, click chemistry, anticancer, terminal alkynes: imidazo [1,2-a] pyrimidine